2010
DOI: 10.1016/j.ccr.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrins as molecular electronic components of functional devices

Abstract: The proposal that molecules can perform electronic functions in devices such as diodes, rectifiers, wires, capacitors, or serve as functional materials for electronic or magnetic memory, has stimulated intense research across physics, chemistry, and engineering for over 35 years. Because biology uses porphyrins and metalloporphyrins as catalysts, small molecule transporters, electrical conduits, and energy transducers in photosynthesis, porphyrins are an obvious class of molecules to investigate for molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
315
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 464 publications
(319 citation statements)
references
References 166 publications
0
315
0
4
Order By: Relevance
“…7,[9][10][11] One important group of such organic molecules are porphyrins, which have numerous technological applications due to their versatile functionalities and distinct chemical and physical properties. 12,13 During the past few years, extensive attention has been paid to porphyrins self-assembled on metal surfaces in order to gain more information about their electronic properties, inherent conformational flexibility and reactivity. 4,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] It has been demonstrated that the adsorption behaviour of porphyrins, such as intramolecular conformation and supramolecular arrangement, is strongly dependent on the actual substrate, 5,21,28 the coverage of these molecules, 22 the surface temperature 4,23,29 and the functional side groups of the porphyrin macrocycle.…”
Section: Introductionmentioning
confidence: 99%
“…7,[9][10][11] One important group of such organic molecules are porphyrins, which have numerous technological applications due to their versatile functionalities and distinct chemical and physical properties. 12,13 During the past few years, extensive attention has been paid to porphyrins self-assembled on metal surfaces in order to gain more information about their electronic properties, inherent conformational flexibility and reactivity. 4,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] It has been demonstrated that the adsorption behaviour of porphyrins, such as intramolecular conformation and supramolecular arrangement, is strongly dependent on the actual substrate, 5,21,28 the coverage of these molecules, 22 the surface temperature 4,23,29 and the functional side groups of the porphyrin macrocycle.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in such systems, proteins are replaced by metalloporphyrins which can mimic the structure and/or the activity of the prosthetic groups of enzymes (Traylor, 1991). Another area of applications of such assembled porphyrins systems consists in the field of nanomaterials, the electronic communication between the macrocycles allowing developments of molecular photonic, electronic or optoelectronic devices (Jurow et al, 2010). Finally, nanocomposite porphyrins-based materials have also been investigated for applications involving energy storage systems, fuel cells and sensors (Di Natale et al, 2010;Ma et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Both are crucial for molecular electronics, catalysis, and photovoltaics. [4][5][6][7][8][9] The properties of the molecule and their interaction with the surface can be tuned with functional chemical groups. Especially important are the so-called anchoring groups that show a strong adsorption to the substrate and are used for the immobilization of molecules on surfaces, which is essential for stable interfaces.…”
Section: Introductionmentioning
confidence: 99%